SPEECH ACT FOUND IN “ALADDIN” MOVIE - Sixtin Ilma Santia; Ferry Kurniawan (Politeknik Negeri Sriwijaya, 2019)
The objective of this study is to explain about speech act in “Aladdin” movie. The writer used qualitative as method of the study. To collect the data, firstly the writer searched for “Aladdin” movie and its script. Secondly, the writer watched the movie thoroughly to understand the content and the situation in the movie. Thirdly, the writer read the script to understand the content and pay attention to each characters’ utterances. Lastly, the writer selected the utterances that contain speech act. In addition, the steps for analyzing the data were; analyzed the data by classifying the utterances that were refer to locutionary, illocutionary, and perlocutionary acts, and then the writer grouped the utterances into direct or indirect speech act. Last, the writer drew some conclusions and wrote a full report about the study. A total of 383 dimensions of speech act were found. It contained 317 utterances and 66 actions which caused by the utterance. They are divided into locutionary 148 uteraces or (38,64%), illocutionary 169 utterances or (44,13%), and perlocutionary 66 actions or (17,23%). For direct speech act there are 183 utterances or (57,73% ), while indirect speech act 134 utterances or (42,27% ).